2019
DOI: 10.1002/jmri.26700
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR spectroscopy in the breast: Technical innovations and clinical applications

Abstract: Proton magnetic resonance spectroscopy (MRS) is a promising noninvasive diagnostic technique for investigation of breast cancer metabolism. Spectroscopic imaging data may be obtained following contrast‐enhanced MRI by applying the point‐resolved spectroscopy sequence (PRESS) or the stimulated echo acquisition mode (STEAM) sequence from the MR voxel encompassing the breast lesion. Total choline signal (tCho) measured in vivo using either a qualitative or quantitative approach has been used as a diagnostic test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 111 publications
0
50
1
Order By: Relevance
“…High choline signal is regarded as a biomarker of elevated lipid membranes turnover and proliferation 53 . Moreover, choline is an established biomarker of malignancy, especially in breast cancer 54 and proposed as a biomarker of malignancy in RCC 55 . Choline compounds are present in healthy renal tissue 56 .…”
Section: Discussionmentioning
confidence: 99%
“…High choline signal is regarded as a biomarker of elevated lipid membranes turnover and proliferation 53 . Moreover, choline is an established biomarker of malignancy, especially in breast cancer 54 and proposed as a biomarker of malignancy in RCC 55 . Choline compounds are present in healthy renal tissue 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Proton ( 1 H) MRS measures metabolites such as total choline (tCho), which is elevated in breast cancers due to increased cellular membrane turnover. 95 Small studies found that decreases in tCho signal during chemotherapy were associated with treatment response [96][97][98] (Fig. 13).…”
Section: Future Directionsmentioning
confidence: 99%
“…MRS can noninvasively assess tumor microenvironment metabolism by measuring signal form metabolites such as the levels of total choline-containing metabolites (tCho) from Proton ( 1 H) MRS in breast [77]. High tCho level indicated cell membrane proliferation, therefore, it could be a marker for evaluating the early tumor response to NAT.…”
Section: Mr Spectroscopy (Mrs) and Blood Oxygen Level-dependent Mrimentioning
confidence: 99%
“…Before and during NAT, lymph node pCR can be predicted by negative hormone receptor and positive HER2 receptor status [103][104][105], lower clinical T and N stage [103], higher histological/nuclear grade [103], and treatment response to NAT of breast primary lesions [106,107]. According to the study by Osorio-Silla [77], 59.7% of patients with primary lesions complete response on MRI also achieved complete response on axillary lymph node, and 75.9% of patients with non-complete response of breast primary tumors on MRI had residual lymph node disease after surgery. Many studies [104,106,107] have similar results, indicating the importance of MRI complete response in primary lesion rate is an important independent for predicting of axillary pCR.…”
Section: Lymph Node Response Evaluationmentioning
confidence: 99%